Can Access to Social Facility Help Poverty Reduction in Agricultural Sector? Evidence from Indonesia - Muhammad Arsyad; Yoshio Kawamura; Syarifuddin Yusuf; Muh. Hatta Jamil; Andi Nuddin; Alimuddin Laapo (Hasanuddin University, 2017)
Poverty in agricultural sector is still becomes a serious issue in developing country, and Indonesia is no exception. Our previous study was focusing on poverty and income (income poverty). This paper, however, deals with a substantive question, can access to social facility (non-income) help poverty reduction in agriculture? The study (also) utilized previous model of Dimensionality Test, Factor and Path Analysis to answer the question. The results show that the higher government transfer source income in terms of Social safety Net Program, the more money for smallholders will be. This leads us to argue that transfer income from the government to the smallholder community can be still considered in maintaining smallholders’ daily life, means helping them move out poverty. The better access to social services such as primary public health center (called PUSKESMAS), clean water supplied by PDAM (Local Government Division for Drinking Water Affairs) and secondary school is, the higher the household income will be. Thus, if PUSKESMAS, primary and secondary schools as well as clean water sources are nearer, the less time and money will be spent to travel, then the more household income at hand will be saved. In other words, distance and degree of utilization appear to be a crucial part of these interpretations above. Therefore, it is reasonable to say that the better the access to social services such as public health center, schools and public clean water, the more household income will be and in turn it will alleviate the poverty of smallholders. It is clear that providing better access to social facility can help poverty reduction in agricultural sector.